Donald Trump is not a Shameless Toddler: The Problems with Psychological Analyses of the 45th US President - Jill Locke (University of Groningen Press, 2019)
This essay critically analyzes two dominant narratives that explain and lament the rise of Donald Trump in the United States. First, I extend Jill Locke’s (2016) concept of “The Lament that Shame is Dead" to show the limitations of criticizing Trump in terms of the “death of shame.” I then turn my attention to the problems inerent in recent characterizations of Trump as a petulant child. Drawing from Locke (2016) on shame and Freud (1914) and Lee Edelman (2004) on the politics of “the child,” I argue that characterizing Trump as shameless, childish, or as a shameless child only affirms, rather than deposes, Trump’s right-wing populist strategy and keeps the focus on him as a personality rather than on the broader social and political context in which he emerged. I argue this has implications for the rise of right-wing populism in the West, more broadly.